Therapeutic potential of niacin in Alzheimer's disease: Nonhuman/Target identification and validation studies: Other. (7th December 2020) - Moutinho, Miguel; Tsai, Andy P.; Puntambekar, Shweta S; Patel, Jheel; Lin, Peter B.; Jadhav, Vaishnavi; Williams, Roxanne Y; Shekhar, Anantha; Landreth, Gary E.
Abstract: Background: Dietary intake of niacin reduces the risk of Alzheimer's disease (AD) and protects against age‐related cognitive decline. Niacin is a ligand for the niacin receptor HCAR2, which, in the brain, is selectively expressed by microglia. HCAR2 activation has been shown to be neuroprotective in stroke and demyelination models. Therefore, we hypothesized that niacin administration could have beneficial effects in AD pathology. Method: 5 month‐old 5xFAD mice, an animal model of AD, were treated with a FDA‐approved formulation of niacin (Niaspan ® ) daily, by oral gavage for 30 days with 100 mg niacin/kg. After treatment, the animals were sacrificed and the brains were collected for immunohistochemistry and biochemical analysis. Gene expression and Aβ uptake efficiency were analyzed in primary cultures of microglia incubated with 1.25 nM of Niaspan ® . Result: Our results indicate there is an induction of HCAR2 expression in the AD brain, prominently in activated microglia. Niaspan ® treatment significantly reduced Aβ burden and number of compact plaques in 5xFAD brain. Accordingly, Niaspan ® induced phagocytic genes and Aβ uptake in primary cultures of microglia. Importantly, Niaspan ® exerted a neuroprotective effect evidenced by reduced neuronal loss in the subiculum and cortical layer 5 of Niaspan ® ‐treated mice, accompanied by a rescue of working memory deficits. Conclusion: These preliminary data suggest that Niaspan ® treatment has neuroprotective effects in AD, even after the onset of severe amyloid pathology, through an induction of Aβ cleareance by microglia. Niaspan ® is a FDA‐approved drug, thus there is a translational potential of this strategy into clinical practice, supporting further study of this therapeutic approach.